KINERJA DAYA SAING KOMODITAS SEKTOR AGROINDUSTRI INDONESIA - Dyah Maya Nihayah (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2012)
International trade has developed very rapidly in recent years. In fact, Indonesia' export reaches US 11,8million in August 2010, especially from non oil export. That's the highest during the Indonesia's trade.Agroindustry sector can be the alternative to open the opportunities of efficient market. That's refers toachievement the economics of scale, due to using the local raw materials. Based on that, this research aimed toidentified the competitiveness of agroindustry's commodities. The data taken from the Standard Classification ofIndonesian Business Field (KBLI) in the Central Bureau of Statistics in 2009 and the Standard InternationalTrade Classification (SITC) 3 Digits from Comtrade, United Nations during 2005- 2009. Competitivenessperformance measured by the Revealed Comparative Advantage (RCA), and the Revealed SymmetricComparative Advantage (RSCA). The result showed 3 commodities, namely 'non soft' vegetable oils (SITC 422),natural rubber (SITC 231) and cocoa (SITC 072), that have the highest index of RCA and RSCA continouslyduring 2005-2008. Other outcomes indicates the decline of commodities that have Indonesia's market share isbigger than the world's market share. Appropriate policies are needed to select commodities which have a highscale economies and competitiveness in international marketKey words : comparative, RCA, RSCA, agroindustry